The comet assay in Ceraeochrysa claveri (Neuroptera: Chrysopidae): A suitable approach for detecting somatic and germ cell genotoxicity induced by agrochemicals - Gastelbondo-Pastrana, Bertha Irina [UNESP]; Fernandes, Fábio Henrique [UNESP]; Salvadori, Daisy Maria Fávero [UNESP]; Santos, Daniela Carvalho dos [UNESP] (Elsevier, 2019)
Some agrochemicals are genotoxic to several organisms. Nevertheless, few protocols are currently available for measuring the toxicogenetic effects of these compounds in target and non-target field-collected species of insects important to agriculture. Herein, we used the species Ceraeochrysa claveri (Neuroptera: Chrysopidae), a non-target predator insect, to investigate the ability of an azadirachtin-based biopesticide (Azamax™) to induce DNA damage. The alkaline version of the comet assay was standardized to evaluate genetic instability caused by the toxicant in somatic (gut) and germ (nurse cells and oocytes) cells of C. claveri. For this, C. claveri larvae were distributed into three groups (10/each) and treated with Azamax™ at 0, 0.3% or 0.5% throughout the larval stage. DNA damage (tail intensity) was measured in adult insects, four days after emerged. The data showed that both doses of Azamax™ (0.3% and 0.5%) were able to significantly (p < 0.05) increase DNA damage in somatic and germ cells of C. claveri. In conclusion, C. claveri (intestinal and ovarian cells) was a sensitive bioindicator for identifying Azamax™ genotoxic potential, whereas the comet assay was a useful tool for detecting the genotoxic hazard of the pesticide in the field-collected insect species. Given that estimation of adverse effects of pollutants on ecosystems is an essential component of environmental risk assessment, the approach used can be recommended to estimate the ecotoxicity of agricultural chemicals.
Keywords: Azadirachtin; Biopesticide; DNA damage; Ecotoxicity; Gut; Ovary